Restructuring of emergent grain boundaries at free surfaces – An interplay between core stabilization and elastic stress generation - Boland, John (My University, 2022)
Emergent grain boundaries at free surface impact a wide range of material properties but little is known about their atomic-scale behavior. Using scanning tunneling microscopy and calculations, we studied the structure of emergent grain boundaries at the surfaces of planar nanocrystalline copper (111) films and bicrystals. We show that for a wide range of misorientation angles there exists a strong energetic preference for boundary cores to lie along close-packed planes that leads to the restructuring of emergent grain boundaries at free surfaces and involves the rotation of adjoining grains and the generation of elastic stresses in the triple junction region. The interplay of the stress field and the core stabilization determines the length scale of the restructuring, which can extend to depths of 15 nm for low angle boundaries. These results point to a new universal mechanism of boundary relaxation at metal surfaces that is expected to be important in grain coalescence, film stress evolution and in controlling properties of nanoscale materials.
PUBLISHED